Malaria mortality in Brazil: an age-period cohort study - Lucas Casagrande Passoni Lopes (Malaria Journal)
Abstract Background Malaria is a parasitic disease caused by protozoa of the genus Plasmodium, transmitted through the bites of Anopheles mosquitoes. Despite significant progress in malaria control, the disease remains a persistent public health challenge, particularly in specific Brazilian regions where environmental and socioeconomic factors contribute to its transmission. Understanding mortality trends across different age groups, periods, births cohorts, and regions is essential for developing targeted intervention strategies and optimizing resource allocation. This study aimed to analyse malaria mortality trends in Brazil, focusing on regional differences using an age-period cohort (APC) model. Methods This ecological study analysed malaria mortality data in Brazil from 1980 to 2024, sourced from DATASUS. Population estimates by sex were retrieved from the Instituto Brasileiro de Geografia e Estatística. Mortality data, including age, year of death, Brazillian macrorregions and admnistratvive Brazilian Amazon legal, as well as the cause of death (ICD-9: 084; ICD-10: B50—B53), were analysed using an APC model. A Poisson distribution was assumed for mortality counts, and analyses were conducted using Holford’s method and its adaptations. Results In the North region, malaria mortality showed an age-related increase, with the highest rates observed in individuals over 80 years old. A significant decline in mortality was observed over the study periods, particularly from 1980 to 1985 to 2020–2024. In the Midwest, the period effect showed fluctuations with an overall decline in recent decades. In the Northeast and Legal Amazon regions, age, period, and cohort effects highlighted clear trends of decreasing mortality over time, particularly for younger cohorts. Conclusion Malaria mortality is influenced by age, period, cohort, and regions. The regional disparities emphasize the need for localized strategies, considering demographic shifts and epidemiological patterns. By integrating these findings into public health planning, policymakers can enhance malaria surveillance, improve healthcare access in vulnerable regions, and refine control measures to further reduce mortality. The study underscores the necessity of continuous investment in malaria prevention, particularly for older adults in endemic areas, to sustain progress and mitigate resurgence risks.